ChatGPT is fun, but not an author - Thorp, H Holden (Science (American Association for the Advancement of Science), 2023)
In less than 2 months, the artificial intelligence (AI) program ChatGPT has become a cultural sensation. It is freely accessible through a web portal created by the tool's developer, OpenAI. The program-which automatically creates text based on written prompts-is so popular that it's likely to be "at capacity right now" if you attempt to use it. When you do get through, ChatGPT provides endless entertainment. I asked it to rewrite the first scene of the classic American play , but to feature Princess Elsa from the animated movie as the main character instead of Willy Loman. The output was an amusing conversation in which Elsa-who has come home from a tough day of selling-is told by her son Happy, "Come on, Mom. You're Elsa from . You have ice powers and you're a queen. You're unstoppable." Mash-ups like this are certainly fun, but there are serious implications for generative AI programs like ChatGPT in science and academia.